VR trainee: A virtual reality training tool for the energy industry - Carvalho, A.; Moreira, W.; Sousa, F; Alexandre, I. (Proceedings - 2025 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops, VRW 2025, 2025)
Operating hazardous machinery often requires comprehensive training, which can be costly, time-consuming, and lead to delays. To address these challenges, we introduce VR Trainee, a Virtual Reality-based tool designed for electrical substation workers. VR Trainee allows users to interact with objects in a safe, controlled environment, enhancing training effectiveness for new maintenance employees. Equipped with inertial sensors, it gathers data to provide real-time feedback related to users’ actions. Initial validation shows significant skill improvements, thanks to trial-and-error opportunities and clear instructions. Our work demonstrates VR’s potential to streamline learning and boost user motivation.